Butein protects the nonalcoholic fatty liver through mitochondrial reactive oxygen species attenuation in rats. (19th April 2018) - Alshammari, Ghedeir M.; Balakrishnan, Aristatile; Chinnasamy, Thirunavukkarasu
Abstract: One of the worldwide metabolic health dilemma is nonalcoholic fatty liver diseases (NAFLD). Researchers are searching effective drug to manage NAFLD patients. One of the best way to manage the metabolic imperfection is through natural principal isolated from different sources. Butein, a natural compound known to have numerous pharmacological application. In the current study we assessed the therapeutic effect of butein administration on liver function tests, oxidative stress, antioxidants, lipid abnormalities, serum inflammatory cytokines, and mitochondrial reactive oxygen species levels, in rats with methionine‐choline deficient (MCD) diet induced NAFLD. Male Wistar rats were treated with MCD diet with/without butein (200 mg/kg body wt. orally) for 6 weeks. The protective effect of butein, were evident from decreased transaminase activities, restoration of albumin, globulin, albumin/globulin ratio, and oxidants in serum ( P < 0.01), further it improved liver antioxidant status ( P < 0.01). Butein significantly lowered lipid profile parameters ( P < 0.01), suppressed inflammatory cytokines ( P < 0.01), and improved liver histology. Further to understand the possible mechanism behind the hepatoprotective and lipid lowering effect of butein, the activities of heme oxygenase (HO1), myeloperoxidase (MPO), and mitochondrial reactive oxygen species (ROS) were measured. We found that butein supplementation significantly decreased the activity of HO1 ( P < 0.001), and increased the activity of MPO ( P < 0.001). Furthermore butein attenuated mitochondrial ROS produced in NAFLD condition. Present study shows that butein supplementation restore liver function by altering liver oxidative stress, inflammatory markers, vital defensive enzyme activities, and mitochondrial ROS. In summary, butein has remarkable potential to develop effective hepato‐protective drug. © 2018 BioFactors, 44(3):289–298, 2018